2012
DOI: 10.1074/jbc.m112.423202
|View full text |Cite
|
Sign up to set email alerts
|

The First Structure of Polarity Suppression Protein, Psu from Enterobacteria Phage P4, Reveals a Novel Fold and a Knotted Dimer

Abstract: Background: Phage P4 Psu protein is a capsid decoration protein with unknown structure. Results: The first structure of Psu reveals a novel fold and a knotted dimer. Conclusion: The V-shaped molecular architecture is important for capsid binding. Significance: The structure of Psu will help to design peptide fragments, which can be used as drugs against the bacterial transcription machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…On activation of OH-radical generation, we observed that only Fe-BABE conjugated to the 181 position of Psu produced two cleavage products near/at 153 and 205 amino acids positions of Rho (Figure 3B). This cleavage product arose due to the vicinity of this C-terminal helix 7 [marked in red, Figure 3A (12)] of Psu to Rho, and it is consistent with the functional importance of this helix in the anti-termination process (11). The cleavage site on Rho, the amino acid 153, is located close to the position of N151D suppressor.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…On activation of OH-radical generation, we observed that only Fe-BABE conjugated to the 181 position of Psu produced two cleavage products near/at 153 and 205 amino acids positions of Rho (Figure 3B). This cleavage product arose due to the vicinity of this C-terminal helix 7 [marked in red, Figure 3A (12)] of Psu to Rho, and it is consistent with the functional importance of this helix in the anti-termination process (11). The cleavage site on Rho, the amino acid 153, is located close to the position of N151D suppressor.…”
Section: Resultssupporting
confidence: 66%
“…(i) The distance between the two C-terminal tail located diametrically opposite direction from the ‘V’-shaped structure of Psu dimer [(12) Supplementary Figure S7A)]. (ii) The electron microgram of a Psu dimer covering the central hole of the hexameric capsid protein, Sid [(7) Supplementary Figure S7B)].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations